Decarbonization of Maritime Transport: Analysis of External Costs - Czermański, Ernest; Pawłowska, Barbara; Oniszczuk-Jastrząbek, Aneta; Cirella, Giuseppe T. (Frontiers in Energy Research, 2020)
For Europe, transport for centuries been a catalyst of economic development. It facilitates commercial exchange among European Union (EU) Member States and much of the rest of the world. Maritime transport forms the main axis of international exchange, carrying approximately 90 % of total traded tonnage. In doing so, it pays the price of being responsible for 2.5 % of worldwide greenhouse gas emissions. The efforts to reduce the negative environmental impact of transport activity are centered on better modal integration of the common transport system, sustainability, green technologies in the transport sector, resource efficiency, and carbon emissions reduction. The International Maritime Organization has tasked its members to achieve a 70 % reduction in CO2 emissions by 2050 or, if possible, to eliminate them altogether. From a business end, it is possible to apply a variety of technologies to ensure zero-emissions or, at the least, a dramatic reduction of emissions in shipping. The aim of this paper is to evaluate the strategic approach to the decarbonization process based on EU strategic documents and low-emission and zero-emission technologies, used and developed, in maritime transport. An estimation of external costs incurred by maritime transport will allow for the assessment of benefits resulting from the application of technologies and alternative fuels proposed in the solutions. On the basis of the obtained results from external cost valuation, it will be possible to estimate the potential for decarbonization in maritime transport.